Multiple-warehouse sliding mode control with a predefined demand trajectory profile - Adamiak. Katarzyna; Zwierzchowski, Tymoteusz (Zielona Góra: Uniwersytet Zielonogórski)
The paper discusses the inventory management problem with a single product stored in two warehouses, where each has its unique suppliers with certain lead times. Moreover, one of the warehouses may act as a backup supplier for the other. In other words, product exchange between two different warehouses within one company is allowed. The first warehouse operates under an "a priori" known time-variant contractual demand and a bounded random one. Its secondary goal is to accumulate emergency stock that can be delivered to the second warehouse within one time period.
Keywords: control design; discrete-time systems; inventory control; model reference control; sliding mode control